Peranan Modal dan Tenaga Kerja Terhadap Produksi Industri Kerajinan Patung Kayu di Kabupaten Badung - I Pande Gede Agus Eka Prananda; I G A A Wulandari; Ni Putu Rediatni Giri (Warmadewa Economic Development Journal (WEDJ), 2023)
This study aims to analyze the role of capital and labor simultaneously on the production of the wooden sculpture industri in Badung Regency, to analyze the role of capital and labor partially on the production of the wooden sculpture industri in Badung Regency. This study uses quantitative data types which include Capital, Labor and Total Production. Collecting data through study documentation, observation, interviews, and questionnaires. The data analysis technique used multiple linear regression analysis technique (Cobb-Douglas). According to the analysis, it was found that 1) Capital and labor variables had a significant effect on the production of the wooden sculpture industry in Badung Regency, 2) The capital variable had a positive effect on the production of the wooden sculpture industry in Badung Regency, 3) The labor variable had a positive effect on industrial production. wooden sculpture in Badung Regency.